Genome editing of an African elite rice variety confers resistance against endemic and emerging Xanthomonas oryzae pv. oryzae strains - Van Schepler-Luu; Coline Sciallano; Melissa Stiebner; Chonghui Ji; Gabriel Boulard; Amadou Diallo; Florence Auguy; Si Nian Char; Yugander Arra; Kyrylo Schenstnyi; Marcel Buchholzer; Eliza PI Loo; et al. (eLife)
Bacterial leaf blight (BB) of rice, caused by Xanthomonas oryzae pv. oryzae (Xoo), threatens global food security and the livelihood of small-scale rice producers. Analyses of Xoo collections from Asia, Africa and the Americas demonstrated complete continental segregation, despite robust global rice trade. Here, we report unprecedented BB outbreaks in Tanzania. The causative strains, unlike endemic African Xoo, carry Asian-type TAL effectors targeting the sucrose transporter SWEET11a and iTALes suppressing Xa1. Phylogenomics clustered these strains with Xoo from Southern-China. African rice varieties do not carry effective resistance. To protect African rice production against this emerging threat, we developed a hybrid CRISPR-Cas9/Cpf1 system to edit all known TALe-binding elements in three SWEET promoters of the East African elite variety Komboka. The edited lines show broad-spectrum resistance against Asian and African strains of Xoo, including strains recently discovered in Tanzania. The strategy could help to protect global rice crops from BB pandemics.